الحذف والترتيب ودورهما في التصرف والتأويل -بين النحو واللسانيات- - سعدية, نعيمة (قــــــراءات, 2019)
تتميز اللغة العربية بخصائص وجدت لنفسها مكانا وفاعلية في اللسانيات الحديثة، كونها تمتلك قواعد إعرابية وآليات نحوية تمنحها القدرة على التصرف، والخروج من معنى إلى معنى آخر، ليفتح  بها باب التأويل النحوي، ومن بين هذه القواعد الإعرابية قاعدتي الحذف والترتيب. وعليه، تحاول هذه الدراسة مقاربة القاعدتين: مفهوما وتمثيلا، مع إبراز دورها في تحقيق التأويل النحوي، كما نسعى فيها إلى إبراز مكانة الحذف والترتيب في الأبنية اللغوية، وفاعلية دورهما في الدرس اللغوي المعاصر، خاصة الأسلوبية واللسانيات النصية وغيرهما.     Abstract : Arabic language is known to have many specifities it had made a place in the modern linguistics; for having grammar rules and mechanisms it gives it the possibility to manage and move from meaning to another. Which gives it the  aportunity of grammatical interprétation, among these grammatical rules we have the omission, and the classification rules. Thus ; This study tries to make a Approachion between these two rules in the context and with illustration ,rather than, showing its in the gramatical interprétation . We are olso trying the role and the place of the omission, and the classification in the linguistical structures, and the efficacity of their rules in the modern language lecture, especially ,stylistics, and textuel linguistics